2014
DOI: 10.1007/s00299-014-1655-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of wheat non-specific lipid transfer proteins involved in chilling tolerance

Abstract: Three TaLTPs were found to enhance chilling tolerance of transgenic Arabidopsis, which were characterized by analyzes of promoter-GUS activity, subcellular localization, chromosomal location and transcriptional profile. Non-specific lipid transfer proteins (nsLTP) are abundantly expressed in plants, however, their functions are still unclear. In this study, we primarily characterized the functions of 3 type I TaLTP genes that were localized on chromosomes 3A, 3B, and 5D, respectively. The transcripts of TaLTPI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 41 publications
1
17
0
1
Order By: Relevance
“…A more encyclopedic review on plant LTPs was published rather recently (2). Nevertheless, it is important to also here point out thatLTPs are suggested to be involved in many other processes in plants, such as signalling (34, 35), defence against biotic hazards (36-40) and tolerance to abiotic stresses just to mention a few examples (12,(41)(42)(43)(44)(45)). …”
mentioning
confidence: 99%
“…A more encyclopedic review on plant LTPs was published rather recently (2). Nevertheless, it is important to also here point out thatLTPs are suggested to be involved in many other processes in plants, such as signalling (34, 35), defence against biotic hazards (36-40) and tolerance to abiotic stresses just to mention a few examples (12,(41)(42)(43)(44)(45)). …”
mentioning
confidence: 99%
“…When deleted to position −297 bp (−297 TaLTP1::uidA construct), the activity in true leaves disappeared completely, but cotyledon expression was not obviously altered until the promoter region was shortened to position −247 bp ( Figure 1c13-c15,c19-c21). Epidermis-specific expression of nsLTPs has been reported for both dicot and monocot plants [12,18,20,32]. Here, we also transformed promoter deletion constructs −400TaLTP1::uidA, −343TaLTP1::uidA, −297TaLTP1::uidA, −247TaLTP1::uidA into a monocot, B. distachyon ( Figure 1c4-c6,c10-c12,c16-c18,c22-c24).…”
Section: Mapping Of a 5'upstream Region Regulating Epidermis-specificmentioning
confidence: 86%
“…Significantly increased expression of TaDIR1-2 under low temperature (4°C) treatment suggests the involvement of TaDIR1-2 in enhancing plant acclimation to abiotic stresses. Cold-inducible expression of LTPs in wheat (Yu et al, 2014), rice (Guo C. et al, 2013), maize (Wei and Zhong, 2014), and Arabidopsis (Xu et al, 2011), indicated that LTPs are strongly associated with cold tolerance in higher plants. It is possible that TaDIR1-2 contributes to cold tolerance by interacting with other proteins to modulate defense responses to abiotic stresses in a ROS-dependent manner.…”
Section: Discussionmentioning
confidence: 99%